Water-based double layer coating transfer aluminum-plated paper material in the application. Issue 1 (May 2021) - Pan, Ruru; Yao, Pingzhang; Yu, Lin; Fang, Xiling
Abstract: This paper introduces a new type of moisturizing paper, which makes the material have a stronger moisturizing effect than ordinary transfer paper through the water-based double-layer coating process. At the same time, the paper has a stronger degradation capacity than plastic film paper, more in line with environmental protection requirements. Through the paper printing machine adaptability verification, the paper has easier processing and stronger printing performance. The development and application of this moistening material is a major innovation in the field of moistening packaging materials research.